Financial barriers and coping strategies: a qualitative study of accessing multidrug-resistant tuberculosis and tuberculosis care in Yunnan, China - C. Hutchison; M. S. Khan; J. Yoong; X. Lin; R. J. Coker (BMC, 2017)
Abstract Background Tuberculosis (TB) and multidrug-resistance tuberculosis (MDR-TB) pose serious challenges to global health, particularly in China, which has the second highest case burden in the world. Disparities in access to care for the poorest, rural TB patients may be exacerbated for MDR-TB patients, although this has not been investigated widely. We examine whether certain patient groups experience different barriers to accessing TB services, whether there are added challenges for patients with MDR-TB, and how patients and health providers cope in Yunnan, a mountainous province in China with a largely rural population and high TB burden. Methods Using a qualitative study design, we conducted five focus group discussions and 47 in-depth interviews with purposively sampled TB and MDR-TB patients and healthcare providers in Mandarin, between August 2014 and May 2015. Field-notes and interview transcripts were analysed via a combination of open and thematic coding. Results Patients and healthcare providers consistently cited financial constraints as the most common barriers to accessing care. Rural residents, farmers and ethnic minorities were the most vulnerable to these barriers, and patients with MDR-TB reported a higher financial burden owing to the centralisation and longer duration of treatment. Support in the form of free or subsidised treatment and medical insurance, was deemed essential but inadequate for alleviating financial barriers to patients. Most patients coped by selling their assets or borrowing money from family members, which often strained relationships. Notably, some healthcare providers themselves reported making financial and other contributions to assist patients, but recognised these practices as unsustainable. Conclusions Financial constraints were identified by TB and MDR-TB patients and health care professionals as the most pervasive barrier to care. Barriers appeared to be magnified for ethnic minorities and patients coming from rural areas, especially those with MDR-TB. To reduce financial barriers and improve treatment outcomes, there is a need for further research into the total costs of seeking and accessing TB and MDR-TB care. This will enable better assessment and targeting of appropriate financial support for identified vulnerable groups and geographic development of relevant services.